Pengaruh Prinsip Good Corporate Governance (GCG) Terhadap Hutang Piutang Berdasarkan Surat Al-Baqarah Ayat 280-283 - Rofidah, Lailia; Yulandari, Miftahul; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
Abstract This research is intended to find out how the influence of the principles of Good Corporate Governance (GCG) on receivables based on Al-Baqarah verses 280-283. This study uses a qualitative descriptive approach as well as primary data & secondary data. Primary data quoted from Al-Qur'an Al-Baqarah verses 280-283, then secondary data was taken from journals, hadiths, books, internet, and other literature. The results of this study are that the principles of GCG, Accounts Payable, and Surah Al-Baqarah verses 280-283 are interconnected and interrelated with one another.The abstract should be in one paragraph.The font is